Analysis of natural convection in a rhombic enclosure with undulations of the top wall – a numerical study. Issue 1 (31st December 2022) - Dutta, Shantanu; Biswas, Arup Kumar; Pati, Sukumar
Abstract : Numerical investigations have been performed in this paper to analyse the natural convection heat transfer, fluid flow and entropy generation aspects for a two-dimensional rhombic enclosure having a wavy top wall of two different number of undulations, heated non-uniformly. The numerical simulations are carried out for three different inclination angle ( φ   = 30°, 45° and 60°) and for 10 3  ≤  Ra  ≤ 10 6 . The results are compared with the enclosure with no undulations at the top wall. We observe that the values of Nu avg at the top wall are less for undulated top wall as compared to respective values for without undulation. It reveals that higher φ always provide higher Nu avg from the top wall. Thermal entropy generation ( Sθ ) is the dominating factor at lower Ra, whereas for higher Ra viscous entropy generation ( Sψ ) is dominating for φ   = 30°. For φ   = 45° and 60°, Sθ is the dominating factor at all Ra .